2015
DOI: 10.1007/s10895-015-1666-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel Spectrofluorimetric Method for the Determination of Perindopril Erbumine Based on Fluorescence Quenching of Rhodamine B

Abstract: A novel, simple and specific spectrofluorimetric method was developed and validated for the determination of perindopril erbumine (PDE). The method is based on the fluorescence quenching of Rhodamine B upon adding perindopril erbumine. The quenched fluorescence was monitored at 578 nm after excitation at 500 nm. The optimization of the reaction conditions such as the solvent, reagent concentration, and reaction time were investigated. Under the optimum conditions, the fluorescence quenching was linear over a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…When the above drugs are added to the dye, a significant quenching of fluorescence intensity has been observed, and increased in an acidic medium has occurred. This may be due to the formation of non-fluorescent ion-pair complexes by electrostatic attraction between medicines and the dye [37,[43][44][45]. The decrease of fluorescence intensity of R-6G is found to be a linear function of Ncontaining medicines concentrations in water solution.…”
Section: Resultsmentioning
confidence: 91%
“…When the above drugs are added to the dye, a significant quenching of fluorescence intensity has been observed, and increased in an acidic medium has occurred. This may be due to the formation of non-fluorescent ion-pair complexes by electrostatic attraction between medicines and the dye [37,[43][44][45]. The decrease of fluorescence intensity of R-6G is found to be a linear function of Ncontaining medicines concentrations in water solution.…”
Section: Resultsmentioning
confidence: 91%
“…This choice of analyte is driven by (a) the importance of detecting PE at ultra-low concentrations due to its pharmacological relevance in the context of hypertension, post-myocardial infarction, and cardiovascular and cerebrovascular disease, 52−56 and (b) its synergistic and specific charge transfer-based interaction with RhB. 56 The 1000-fold SPCE enhancement afforded by AgNCF + GO is one of the highest reported using NCF substrates and is realized through rational synergistic engineering of metal-based plasmonics and dielectric-based EM hotspots with plasmons of extended π-conjugated frameworks (GO). Therefore, this SPCE platform was selected for the qualitative and quantitative detection of PE at ultra-low concentrations, extending to single-molecular limits.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Such synergistic coupling through multi-component integration lowers the Ohmic losses and contributes to unprecedented SPCE enhancements. Furthermore, the sharply directional, highly polarized, and enhanced emissions enable reliable and ultrasensitive detection of pharmacologically important drug (perindopril erbumine, PE) at single-molecular levels (0.1 attomolar) through a mobile phone-based platform, presenting an important capability for treatment of hypertension and myocardial infarction. Thus, the materials and design principles illustrated in this report provide newer fundamental insights for achieving non-plasmonic and yet augmented SPCE enhancements, leading to versatile point-of-care diagnostic platforms.…”
Section: Introductionmentioning
confidence: 97%
“…Remington (Joseph, Alfonso, 2000) and physician's desk reference (Montvale, 2000). A survey of the literature revealed that UV (Nayak, Pillai, 2011;Kale et al, 2011), HPLC(El- Gizawy et al, 2014;Gizawy et al, 2013;Pattan, et al,2013;Singh et al, 2011), RP-HPLC (Chaudhary, Determination of perindopril erbumine by oxidative coupling reaction using 2, 6-dichloroquinone-4-chlorimide Patel, Chaudhary 2010;Mastannamma et al, 2016;Dugga, Peraman, Nayakanti, 2014;Joseph, Philip, 2011;Patel et al, 2011;Prajapati et al, 2011;Prameela Rani, Bala Sekaran, 2009), spectrofluorimetric (Fael Sakur 2015a. ;Fael Sakur 2015b), kinetic spectrophotometric (Rahman, Rahman, Haque, 2017;Rahman, Anwar, Kashif, 2006), LC-MS (Deepak, et al,2006) and GC-MS (Maurer, Kraemer, Arlt,1998) methods were reported for the estimation of PPE.…”
Section: Introductionmentioning
confidence: 99%